ABOUT THE FUNDAMENTAL TRAINING OF SPECIALISTS OF THE AIR-SCIENTIFIC INDUSTRY AT THE NATIONAL AEROSPACE UNIVERSITY «KHAІ» - Александр Владимирович Амброжевич; Сергей Александрович Ищенко; Игорь Федорович Кравченко; Юрий Александрович Крашаница; Владимир Александрович Кудрявцев; Борис Владимирович Лупкин; Виталий Николаевич Павленко; Петр Алексеевич Яковенко (Авіаційно-космічна техніка та технологія, 2017)
The structures and comparative analysis of programs and courses of fundamental training of specialists for the aerospace industry in the USA, Germany, China and KhAI are presented. The instructional-laboratory base of the department of aerohydrodynamics of the National Aerospace University «KhAI» is described in detail and provides information on the scientific and experimental bases of aerodynamic complexes in Ukraine and leading organizations in North America and Western Europe. Some basic results of theoretical and experimental research of the faculty and scientific and technical staff of the Department of aerohydrodynamics of the National Aerospace University «KhAI».